1988
DOI: 10.1901/jaba.1988.21-253
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Self‐protection to Children Using Television Techniques

Abstract: This study compared the effectiveness of a videotape training program with other methods of teaching children self-protection to prevent child abduction. Subjects were kindergarten and first-grade students. Four experimental conditions were presented: videotape with behavior rehearsal, videotape only, a standard safety program, and no training. Acquisition of self-protective behaviors was measured at posttraining and follow-up by having confederate adults entice the children near their schools and homes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 11 publications
3
106
0
1
Order By: Relevance
“…Only a handful of studies has investigated group training of abduction-prevention skills (Carroll-Rowan & Miltenberger, 1994;OlsenWoods et al, 1998;Poche et al, 1988). These studies have demonstrated that there is a need to make group BST more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of studies has investigated group training of abduction-prevention skills (Carroll-Rowan & Miltenberger, 1994;OlsenWoods et al, 1998;Poche et al, 1988). These studies have demonstrated that there is a need to make group BST more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Escaping the situation means putting physical distance between the child and the threat, most often by running away. In most safety threat situations, an immediate response is critical because the longer the child is exposed to the threat without taking action, the more likely the child will be harmed (e.g., Poche, Yoder, & Miltenberger, 1988). For example, when finding a firearm, the child escapes from the situation by running to a parent or other adult (e.g., teacher, babysitter).…”
Section: Types Of Safety Skillsmentioning
confidence: 99%
“…In situ assessments have been shown to be useful for evaluating safety skills in response to other safety threats, including abduction and sexual abuse lures (e.g., Johnson et al, 2005;Poche et al, 1988). The safety skills exhibited by children during these assessments are typically scored numerically.…”
Section: In Situ Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the function of video modelling was isolated from other methods in as natural an environment as possible (e.g., Morgan & Salzberg, 1992). Second, the videotape format used in this study obtained all the advantages of convenience, standardisation, and efficiency that may be difficult to achieve with in vivo formats (Poche, Yoder, & Miltenberger, 1988). Third, not only were short video clips shown to be effective (i.e., 35 secs), but also these video presentations resulted in rapid changes in behaviour, that required no further prompts (in terms of video presentations) in subsequent assessments across other stimuli.…”
Section: Discussionmentioning
confidence: 99%